2011
DOI: 10.1089/apc.2011.0051
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Validity of a Computer-Based Cognitive Screening Tool for Use in Adults with HIV Disease

Abstract: As the incidence of HIV-associated dementia has decreased, the survival of HIV-infected individuals with milder forms of cognitive impairment has increased. Detecting this milder impairment in its earliest stages has great clinical and research importance. We report here the results of an initial evaluation of the Computer Assessment of Mild Cognitive Impairment (CAMCI Ò ), a computerized screening tool designed to assess abnormal cognitive decline with reduced respondent and test administrator burden. Fifty-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 13 publications
1
28
1
1
Order By: Relevance
“…It is also well tolerated by elderly patients with limited computer knowledge and can be completed in 20 min [26]. Furthermore, CAMCI® is a sensitive tool for detecting mild cognitive problems in nondemented patients [26, 49]. To demonstrate the sensitivity of CAMCI® in discerning cognitive difficulties in the cancer population, we incorporated the Stroop test in our study, as it is a widely used test across multiple disciplines including cancer-related fatigue [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also well tolerated by elderly patients with limited computer knowledge and can be completed in 20 min [26]. Furthermore, CAMCI® is a sensitive tool for detecting mild cognitive problems in nondemented patients [26, 49]. To demonstrate the sensitivity of CAMCI® in discerning cognitive difficulties in the cancer population, we incorporated the Stroop test in our study, as it is a widely used test across multiple disciplines including cancer-related fatigue [51].…”
Section: Discussionmentioning
confidence: 99%
“…CAMCI® has good test-retest reliability and has demonstrated good sensitivity (86%) as well as specificity (94%) for the identification of mild forms of cognitive impairment [26, 48]. The sensitivity of CAMCI® was 0.72 relative to the Global Impairment Rating, with good positive and negative predictive values of 0.93 and 0.89, respectively [49]. CAMCI® was administered in English on a touch screen tablet PC at baseline, at midpoint, and at completion of EBRT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, research studies in the United States that have used formal neuropsychometric endpoints have observed a stable overall prevalence of HAND with greater preponderance of milder forms (Heaton et al 2010; Lescure et al 2011). However, these studies often do not represent the general HIV+ population in terms of sociodemographics and lifestyle behaviors (Sacktor et al 2005; Becker et al 2011; Overton et al 2011; Richardson et al 2005). Our study population was unique in that it was composed of all potential HIV+ individuals who attended a general infectious disease clinic.…”
Section: Discussionmentioning
confidence: 99%
“…21 Their significance in HIV clinical practice, particularly as an incidental finding, remains unclear. There have been recent advances in non-imaging tools used to diagnose and monitor NCI in HIV, [22][23][24][25] using techniques that are reproducible and require less expertise than neuropsychological assessment. However, given some of the uncertainty over the longer term clinical importance of mild-to-moderate cognitive difficulties, improved understanding of biomarkers such as structural and functional imaging is vital.…”
Section: Introductionmentioning
confidence: 99%